Nutrition policy in whose interests? A New Zealand case study - Jenkin, Gabrielle; Signal, Louise; Thomson, George (Public health nutrition, 2012)
In the context of the global obesity epidemic, national nutrition policies have come under scrutiny. The present paper examines whose interests - industry or public health - are served by these policies and why. Using an exemplary case study of submissions to an inquiry into obesity, the research compared the positions of industry and public health groups with that taken by government. We assessed whether the interests were given equal consideration (a pluralist model of influence) or whether the interests of one group were favoured over the other (a neo-pluralist model). 2006 New Zealand Inquiry into Obesity. Food and advertising industry and public health submitters. The Government's position was largely aligned with industry interests in three of four policy domains: the national obesity strategy; food industry policy; and advertising and marketing policies. The exception to this was nutrition policy in schools, where the Government's position was aligned with public health interests. These findings support the neo-pluralist model of interest group influence. The dominance of the food industry in national nutrition policy needs to be addressed. It is in the interests of the public, industry and the state that government regulates the food and advertising industries and limits the involvement of industry in policy making. Failure to do so will be costly for individuals, in terms of poor health and earlier death, costly to governments in terms of the associated health costs, and costly to both the government and industry due to losses in human productivity.